A Study of climate change and its impact on tourism - Gaurang Kakkar; Prof. (Dr.) Indrani Chakravorty; Prof. (Dr.) Subhrajit Banerjee (International Journal of Environmental Planning and Development Architecture, 2024)
Tourism is clearly linked to climate, as vacationers wish spending time in open-air and travel to delight in the sky or countryside. It is then amazing that the tourism works pays slight thoughtfulness to climate and climatic transformation. Numerous of investigations on tourism and climate change is, still, beginning to raise. Though it is a generally known statement that climate change can adversely effect on tourism sector and shake the tourism markets at the socio-economic as well, observed investigations on the climate change and tourism expansion connection has been somewhat limited, specifically for the island financial prudence that are seriously reliant on tourism. This exploration purposes to add-on the works on climate change and tourism by realistically measuring the connection among climate change and visitor arrivals. This research analyses this works in this field, conversing failings and current progresses in worldwide modelling of tourism movements are existing. The series of approaches used and glitches considered in the study is enormous, and conclusions are harmoniously varied. Though, most of analysis agrees that climate change affects to tourism. Even though straight effects are foreseeable, subsidiary effects on the multifaceted tourism structure are tougher to get ahead, also the tourism industry must form flexibility to answer back to upcoming revolution.
Keywords: Climate; Climate change; Economics; Tourism; Travel